Robust hippocampal responsivity during retrieval of consolidated associative memory. Issue 5 (10th March 2015) - Hattori, Shoai; Chen, Lillian; Weiss, Craig; Disterhoft, John F.
ABSTRACT A contentious point in memory research is whether or not the hippocampus plays a time‐limited role in the consolidation of declarative memories. A widely held view is that declarative memories are initially encoded in the hippocampus, then transferred to the neocortex for long‐term storage. Alternate views argue instead that the hippocampus continues to play a role in remote memory recall. These competing theories are largely based on human amnesic and animal lesion/inactivation studies. However, in vivo electrophysiological evidence supporting these views is scarce. Given that other studies examining the role of the hippocampus in remote memory retrieval using lesion and imaging techniques in human and animal models have provided mixed results, it would be particularly useful to gain insight at the in vivo electrophysiological level. Here we report hippocampal single‐neuron and theta activity recorded longitudinally during acquisition and remote retrieval of trace eyeblink conditioning. Results from conditioned rabbits were compared to those obtained from yoked pseudo‐conditioned control rabbits. Results reveal continued learning‐specific hippocampal activity one month after initial acquisition of the task. Our findings yield insight into the normal physiological responses of the hippocampus during memory processes and provide compelling in vivo electrophysiological evidence that the hippocampus is involved in both acquisition and retrieval of consolidated memories. © 2014 The Authors Hippocampus Published by Wiley Periodicals, Inc.